2004
DOI: 10.1007/s00484-004-0229-z
|View full text |Cite
|
Sign up to set email alerts
|

Transport of airborne pollen into the city of Thessaloniki: the effects of wind direction, speed and persistence

Abstract: We examined the effect of the wind vector analyzed into its three components (direction, speed and persistence), on the circulation of pollen from different plant taxa prominent in the Thessaloniki area for a 4-year period (1996-1999). These plant taxa were Ambrosia spp., Artemisia spp., Chenopodiaceae, Corylus spp., Cupressaceae, Olea europaea, Pinaceae, Platanus spp., Poaceae, Populus spp., Quercus spp., and Urticaceae. Airborne pollen of Cupressaceae, Urticaceae, Quercus spp. and O. europaea make up approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 19 publications
4
68
0
2
Order By: Relevance
“…This increase may be due to changes in climatic factors or other anthropogenic forces, such as urban or industrial pollution. Pollen maturation, rapture grain and atmospheric dispersal are generally thought to be affected by these variables; however, this may not always be the case [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…This increase may be due to changes in climatic factors or other anthropogenic forces, such as urban or industrial pollution. Pollen maturation, rapture grain and atmospheric dispersal are generally thought to be affected by these variables; however, this may not always be the case [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Starting from the 1990s, episodes of pollen dispersion on regional and continental scales have been addressed in numerous studies (Belmonte et al, 2000;Corden et al, 2002;Damialis and Gioulekas, 2005;Hjelmroos, 1992;Latalova et al, 2002;Mahura et al, 2007;Ranta and Satri, 2007;Ranta et al, 2011;Rantio-Lehtimaki, 1994;Siljamo et al, 2008c;Skjøth et al, 2008;Sofiev et al, 2012bSofiev et al, , 2006aYliPanula et al, 2009; see also reviews by Smith et al, 2014, andBergmann, 2013). It was shown that, although the features of each specific long-range transport episode vary widely, there may be a systematic pattern in the springtime pollen redistribution in Europe with prevailing transport directions, main source and receptor regions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that, although the features of each specific long-range transport episode vary widely, there may be a systematic pattern in the springtime pollen redistribution in Europe with prevailing transport directions, main source and receptor regions, etc. There have been several attempts to reveal such a pattern via a multiannual analysis (Damialis and Gioulekas, 2005;Siljamo et al, 2008aSkjøth et al, 2009Skjøth et al, , 2007Smith et al, 2008;Sofiev et al, 2006a;Yli-Panula et al, 2009) but the picture is still largely incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…There is now a large body of evidence showing that atmospheric transport can result in high atmospheric pollen concentrations and modify pollen season characteristics such as start date and duration (Sofiev et al 2006(Sofiev et al , 2013a, including a number of papers published in IJB on the subject (Damialis et al 2005;Stach et al 2007;Belmonte et al 2008;Šikoparija et al 2009;Skjøth et al 2009;Hernández-Ceballos et al 2011;Izquierdo et al 2011;Kasprzyk et al 2011;Fernández-Rodríguez et al 2014;Grewling et al 2016). It is argued that such atmospheric transport episodes cannot be predicted by the use of local or regional observations, and forecasts need to be constructed at the continental level and include the biological and meteorological mechanisms that control the release and subsequent dispersion of pollen to the atmosphere (Sofiev et al 2006).…”
Section: Aerobiological Modelling and Forecasting In Ijbmentioning
confidence: 99%